Combating crimes in cyberspace and defending the cybercriminals: the malaysian perspective - Mohamed, Duryana (2009)
Cyber crimes are committed regardless of boundaries. The crimes continue to threaten public security and cause problems to Malaysian society and the world at large. These activities, if not controlled, may even collapse the security system of the country. To combat this threat, the society has to play its role by giving information on crimes committed and avoid computer abuses. In Malaysia, the Government, through the Royal Malaysian Police, Cyber Security Malaysia, MIMOS and other agencies, have worked together to ensure those criminals are arrested and punished accordingly. The arrest, prosecution and conviction are made under the relevant laws and procedures such as Computer Crimes Act 1997, Communication and Multimedia Act 1998, the Penal Code, the Criminal Procedure Code and the Evidence Act 1950. The expert evidence will be taken into account when necessary. Nevertheless, the suspect shall also be given an opportunity to defend himself. He shall not be prosecuted and executed if the evidence is insufficient to establish the crime committed. Thus, this paper shall examine the efforts taken by the Malaysian Government in combating cybercrime, the rights of the suspect or the accused and the obligations of the defence counsel in defending his client. Problems and challenges to the investigators, prosecutors, forensic experts and defence counsel will also be highlighted from the Malaysian perspective. For the above purposes, reference shall include relevant practices and procedures as well as decided cases in Malaysia, Singapore and other relevant jurisdictions.